2022
DOI: 10.1177/15248380221129587
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analytic Review of the Impact of Child Maltreatment on Self-Esteem: 1981 to 2021

Abstract: An increasing number of studies have examined the relationship between child maltreatment and self-esteem. In this study, we assess the magnitude of this association through a meta-analytic approach. Four English databases (PubMed, PsycINFO, PsycARTICLES, and Web of Science), three Chinese databases (China National Knowledge Infrastructure, Wanfang, and Weipu), and grey literature were systematically searched. A total of 254 independent studies, including 550 effect sizes, met the inclusion criteria for this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 56 publications
0
6
0
1
Order By: Relevance
“…Results from this study reconfirmed that CM was on average negatively associated with gratitude, and the magnitude of the overall effect size was moderate based on Cohen’s (1988) criteria: r = −.311, [−0.382, −0.235], p < .001. This magnitude is relatively larger than the association of CM with other psychological strengths, such as self-esteem ( r = −.24) (Zhang et al, 2022) and self-compassion ( r = −.28) (Zhang et al, 2021). The potential reason may be that the cognitive ability (i.e., ToM) that is crucial to experience gratitude fully develops around the age of 7 (Froh et al, 2007), and this is the time when the child’s ability to precisely interpret the intention of others fully developed.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Results from this study reconfirmed that CM was on average negatively associated with gratitude, and the magnitude of the overall effect size was moderate based on Cohen’s (1988) criteria: r = −.311, [−0.382, −0.235], p < .001. This magnitude is relatively larger than the association of CM with other psychological strengths, such as self-esteem ( r = −.24) (Zhang et al, 2022) and self-compassion ( r = −.28) (Zhang et al, 2021). The potential reason may be that the cognitive ability (i.e., ToM) that is crucial to experience gratitude fully develops around the age of 7 (Froh et al, 2007), and this is the time when the child’s ability to precisely interpret the intention of others fully developed.…”
Section: Discussionmentioning
confidence: 77%
“…relatively larger than the association of CM with other psychological strengths, such as self-esteem (r = −.24) (Zhang et al, 2022) and self-compassion (r = −.28) (Zhang et al, 2021). The potential reason may be that the cognitive ability (i.e., ToM) that is crucial to experience gratitude fully develops around the age of 7 (Froh et al, 2007), and this is the time when the child's ability to precisely interpret the intention of others fully developed.…”
Section: The Overall Association Between CM and Gratitudementioning
confidence: 85%
“…The lack of emotional interaction and parental care may result in alterations to neural circuits involved in cognitive processes, leading to potential impairments in cognitive function. Second, emotionally neglected children may feel unloved and unwanted, fear emotional closeness, and shun intimacy in relationships, which puts them at risk of low self-esteem and emotional problems, such as depression and anxiety throughout their lives (Strathearn et al, 2020; Zhang et al, 2022). Third, research has shown that individuals with these psychosocial factors may experience lower learning motivation and poorer self-perception (Zhang et al, 2020), which further affect their cognitive function, including attention, motivation, and information processing.…”
Section: Childhood Emotional Neglect and Cognitive Functionmentioning
confidence: 99%
“…In addition, these employees believe that they have a certain degree of power in the overall organization and have an important and unique existence value. Current studies have shown that employees' organizational self-esteem is positively correlated with job performance (Sun, Gao, & Avolio,2023) [5]. Because employees have a high degree of organizational selfesteem, the more responsive they are to the organization.…”
Section: Introductionmentioning
confidence: 99%